Self-administered structured food record for measuring individual energy and nutrient intake in large cohorts : design and validation - García, Silvia M.
Introduction: Several instruments developed to assess dietary intake of groups or populations have strengths and weaknesses that affect their specific application. No self-administered, closed-ended dietary survey was previously used in Argentina to assess current food and nutrient intake on a daily basis. Objective: To design and validate a self-administered, structured food record (NutriQuid, NQ) representative of the adult Argentine population’s food consumption pattern to measure individual energy and nutrient intake. Materials and methods: Records were loaded onto a database using software that checks a regional nutrition information system (SARA program), automatically quantifying energy and nutrient intake. NQ validation included two phases: (1) NQ construct validity comparing records kept simultaneously by healthy volunteers (45---75 years) and a nutritionist who provided meals (reference), and (2) verification of whether NQ reflected target population consumption (calories and nutrients), week consumption differences, respondent acceptability, and ease of data entry/analysis. Data analysis included descriptive statistics, repeated measures ANOVA, intraclass correlation coefficient, nonparametric regression, and cross-classification into quintiles. Results: The first validation (study group vs. reference) showed an underestimation (10%) of carbohydrate, fat, and energy intake. Second validation: 109 volunteers (91% response) completed the NQ for seven consecutive days. Record completion took about 9 min/day, and data entry 3---6 min. Mean calorie intake was 2240 ± 119 kcal/day (42% carbohydrates, 17% protein, and 41% fat). Intake significantly increased in the weekend. Conclusion: NQ is a simple and efficient tool to assess dietary intake in large samples.